Efektivitas Implementasi Program Cadangan Pangan Pemerintah (CPP) dalam Mendukung Ketahanan Pangan Keluarga Rentan di Desa Godog, Kecamatan Laren, Kabupaten Lamongan - Ervan Yuliansyah; Ika Devy Pramudiana; Widyawati Widyawati; Sapto Pramono (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2025)
This study aims to analyze the effectiveness of implementing the Government Food Reserve (CPP) program in supporting the food security of vulnerable families in Godog Village, Laren Subdistrict, Lamongan Regency. Since 2022, the CPP program has been designed to assist communities affected by food insecurity by providing food aid in the form of 10 kg rice packages. The study employs a qualitative approach with a descriptive research type. The focus lies on analyzing the program’s implementation and the factors influencing its success, using Edward III’s theory, which includes four key elements: communication, resources, disposition, and bureaucratic structure. Data were collected through in-depth interviews, participatory observation, and documentation involving beneficiaries, village officials, and aid distribution personnel. The findings indicate that the CPP program in Godog Village has significantly benefited vulnerable families by improving their food security but still faces several challenges. Good communication between the village government and the community, as well as the availability of resources, serve as the primary supporting factors for smooth aid distribution. Conversely, the main challenges arise from poor road infrastructure, which hampers aid distribution, and issues in updating the Beneficiary Family (KPM) data. The study recommends improving infrastructure and updating KPM data as strategic steps to enhance the program’s implementation effectiveness.